Hubungan Pengetahuan Dan Sikap Perawat Tentang HIV-AIDS Dengan Tindakan Perawat Pada Penderita HIV-AIDS - Nelfa Fitria Takahepis (FKIP, Universitas Palangka Raya, 2022)
Based on (UNAIDS) Global Statistics in 2018 recorded that 36.9 million people in the world are living with HIV Human Immunodeficiency Virus (HIV) is a virus that could weaken immunity in humans. The HIV/AIDS issue around the world continues to increase.. Nurses have a significant role in efforts to maintain the health quality of HIV/AIDS patients. Awareness and a positive attitude are crucial to maximize care and increase comfort in care providers. The purposes of this study was to determine the correlation between the nurses' awareness and attitudes toward HIV-AIDS with the nurse's actions toward HIV-AIDS patients in Robert Wolter Mongisidi Tk. II Hospital Manado City. This study conducted using a descriptive-analytical research method that is cross-sectional which aims to obtain information. The sample is taken from respondents as many as 31 respondents using total sampling. Data collection is done by giving a questionnaire. Furthermore, the data that has been collected is processed using the SPSS version 16.0 computer program to be analyzed using the Fisher's Exact Test statistical test with a significance level (α) 0.05. The results show that as many as 26 (83.9) nurses had a good awareness, 22 (71.0) nurses had good attitudes, and 23 (74.2) nurses had good actions. The Chi-square statistic test aqcuire P value of awareness was 0.002 (α≤0.05), and the P value for Attitude was 0.003 (α≤0.05). This study concluded that there is a significant correlation between the nurse’s awareness of Hiv-Aids and the actions of nurses in patients with Hiv-Aids. Also, there is a correlation between the nurse’s attitudes of Hiv-Aids and the actions of nurses in patients with HIV-AIDS.